Pedestrian Bridge Design with IPE beams - Getial Rivera, Sofía Liliana; Ibarra Muñoz, Miguel Ángel; Pantoja Zambrano, Kevin Alejandro (Boletín Informativo CEI, 2020)
The objective of this project is to design a pedestrian bridge that ensure the security of the people who want to cross the street at Las Americas Avenue in San Juan de Pasto, Colombia. In the first place, a hydraulic platform at the ends of the structure to help disabled people to cross the bridge will be used. Also, the structural analysis will be used to solve the structure with Cross method. Finally, to obtain the deflection of the beam Python software will be used.